Functional Response of the Parasitoid Eriborus argenteopilosus (Cameron) to Crocidolomia pavonana (Fabricius) under Different Temperature - NOVRI NELLY; TRIMURTI HABAZAR; RAHMAT SYAHNI (HAYATI Journal of Biosciences, 2005)
The functional response of the parasitoid Eriborus argenteopilosus (Cameron) (Hymenoptera: Ichneumonidae) were studied using Crocidolomia pavonana (Fabricius) (Lepidoptera: Pyralidae) larvae as host at different densities. All larvae were exposed to one E. argenteopilosus female for three hours at three different temperatures, i.e 20 oC, 25 oC, and 30 oC. Data were analyzed using logistic regression to determine the type of functional response. At 20 oC E. argenteopilosus showed type II functional response, while at 25 oC and 30 oC the functional response is type III. Based on surface analysis, the optimal parasitism rate occurred at 22.24 oC with 10.12 larvae parasitized/hour. The larvae density to achieve optimal parasitism rate was 69.38 larvae. The optimal oviposition rate was 12.59 eggs/hour which occurred at 24.41 oC, using a density of 94.54 larvae.